Pengaruh Metode Pembelajaran Mind Mapping Terhadap Minat Belajar Matematika Peserta Didik Pada Materi Perkalian Kelas IV MI Nurul Huda - Kholilatun Najah (CV Edujavare Publishing, 2023)
One of the problems in education that is very influential is due to a decrease in interest in learning from students. The interest in learning students is very crucial and solutions must be found. Because the interest of students will greatly affect the learning achievement of students. Especially in mathematics, English, and general material that some students have difficulty understanding. This study aims to examine